Analisis Kestabilan pada Model Matematika Deradikalisasi - Wimbo Fari Susilo; Lukita Ambarwati; Eti Dwi Wiraningsih (JMT : Jurnal Matematika dan Terapan, 2022)
Radicalization is a process by which individuals adopt political, social, and religious ideologies that lead to violence. Violent behavior in the radicalization process is the reason that radicalism is considered the cause of acts of terrorism. Therefore, to reduce this radicalization process, a deradicalization program is carried out. Deradicalization is an attempt to persuade adherents of radicalism to leave this notion. In order to determine the level of spread of radicalization, a mathematical model of deradicalization was made. The model consists of four compartments, namely, Susceptible, Extrimist, Recruiters, and Treatment. The model is analyzed by determining the equilibrium point and determining the base reproduction number ( ℜ0). If ℜ0<1 then the system will be locally asymptotically stable, and if ℜ0>1 then the system will be unstable. The simulation is carried out with the data that has been obtained, with the individual displacement parameters from the Extrimist compartment to the Treatment compartment with a value of 0.05 and the individual displacement from the Recruiters compartment to the Treatment compartment with a value of 0.165, simulation results show a graph that is stable to the point of endemic equilibrium. Meanwhile, if the value of individual displacement from the Extrimist and Recruiters compartments to the Treatment compartment is 0.5, the simulation results show that the graph gradually goes to zero.